Contribution Index Based on Green Building Certification Systems - Yuting Sun; Bee Hua Goh (Construction Economics and Building, 2015)
Green Building Certification Systems (GBCS) are carried out in many countries due to the rising awareness of the importance of sustainability in the building industry. The intention should have motivated participants to construct and operate buildings sustainably, however, there is not yet a method developed to investigate the motivation of the participants. Based on the GBCS, this paper proposes the contribution index as a standard global method to analyze the performance of participants in the green building industry. Three contribution indices, namely Frequency Contribution Index (FCI), Intensity Contribution Index (ICI) and Comprehensive Contribution Index (CCI) that concern each different category of participant, have been formulated. Three further analyses based on the index were undertaken to investigate some features of the industry. A case study of Singapore was conducted to show how the contribution index could be used to extract industry patterns and trends and assess the participants’ performance in the green building industry. Interviews with experts provide some suggested applications and support for the findings.